2014
DOI: 10.1007/s12665-014-3797-1
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical and multivariate analysis of soil heavy metal contamination near coal mining area, Northeastern India

Abstract: The spatial distribution and hazard assessment of heavy metals in the soils of surrounding agricultural fields affected by mine drainage of Ledo coal mining area of Tinsukia district, Assam, India, were investigated using statistics, geostatistics and geographic information system techniques. The amounts of Cr, Cd, Ni and Pb were determined from 83 soil samples collected within the contaminated area. The maps based on ordinary kriging showed that high concentrations of heavy metals were located in the low-lyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Ni with 24.56 mg/kg is the fourth prominent element, reaching SQGs [33,34]. A similar upraise in concentration is observed in China (29.1 mg/kg) [36,37] and India (83.7 mg/kg) [38,39]. Afterwards, Se (27 mg/kg) is an emerging element, especially in tailings and soils, which is comparable with Iran (23 mg/kg) [40,41], Spain (13mg/kg), and Vietnam (12mg/kg) [46,47].…”
Section: Overall Elemental Concentration and Physical Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…Ni with 24.56 mg/kg is the fourth prominent element, reaching SQGs [33,34]. A similar upraise in concentration is observed in China (29.1 mg/kg) [36,37] and India (83.7 mg/kg) [38,39]. Afterwards, Se (27 mg/kg) is an emerging element, especially in tailings and soils, which is comparable with Iran (23 mg/kg) [40,41], Spain (13mg/kg), and Vietnam (12mg/kg) [46,47].…”
Section: Overall Elemental Concentration and Physical Parameterssupporting
confidence: 65%
“…Cd, a well carcinogenic element, has higher concentrations, like tailings have 3.52 mg/kg and soils have 7.33 mg/kg, while others areas of the Indus basin have lower concentrations of 0.4 mg/kg and 0.3 mg/kg [35]. A higher concentration is comparable with neighboring countries like China (11.0 mg/kg) [36,37] and India (3.82 mg/kg) [38,39]. Sediments of Spain areas also show higher concentration of 6.59 mg/kg [42,43].…”
Section: Overall Elemental Concentration and Physical Parametersmentioning
confidence: 99%
“…However, compositing soil samples prior to chemical analyses allowed for a greater generalization of chemical loads in the study area via kriging. Whether our small sample size was sufficient for accurately interpolating values across the entire study area is unclear; although, empirical Bayesian kriging models are typically accurate with small datasets [ 57 , 58 ] and our cross-validation results suggested that prediction accuracy for each chemical was high [ 58 , 62 – 64 ]. Additionally, RMSSDE and MSDE values indicated that the kriging models accurately estimated the variance in the predictions, though nominally poorer for mercury and TEQs.…”
Section: Discussionmentioning
confidence: 99%
“…We applied all semi-variograms that are available under empirical Bayesian kriging, which are spatial autocorrelation models that predict the relationship of concentrations as a function of distance and direction. We selected the best semi-variogram for each chemical via cross-validation, based on the following goodness-of-fit measures: mean error (ME), mean standardized error (MSDE), mean standard error (MSE), root-mean-square error (RMSE), and root-mean-square standardized error (RMSSDE) [ 58 , 62 – 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Juan and Lee used three nonparametric Kriging methods to delineate heavy metal contaminated soils [ 19 ]. Reza used the ordinary Kriging to estimate the spatial distribution of heavy metals in the soils of surrounding agricultural fields affected by mine drainage [ 20 ]. Hu et al studied on spatial distribution of farmland soil heavy metals using BP neural network [ 21 ].…”
Section: Introductionmentioning
confidence: 99%